Reforma do setor público em São Paulo: 1995-1998 - Hahn, Neide Saraceni (1998)
The author analyzes the proposal, by Covas government, of an institutional reform, its possibilities and limitations, to demonstrate that the process of reform of the State - generally considered - doesn't have universal character. Comparative studies evidence the historical singularity of each experience. In the case of the state of São Paulo, Brazil, the most typical characteristic of government's experience during the period 1995-1998 is the coexistence and complementarity of two processes: the adjustment of public finances and the administrational reform.